Masjid Sebagai Ruang Literasi (Studi Kasus Masjid Jenderal Sudirman Colombo, Sleman, Yogyakarta) - Dwi Adhe Nugraha; Agnes Sunartiningsih (Universitas Darussalam Gontor, 2021)
This study aims to describe descriptively the efforts of the Masjid Jenderal Sudirman (MJS) takmir in providing an open literacy space for the community, starting with the Ngaji Filsafat, which is a mosque recitation activity. Philosophy is the object of this research, namely the recitation that has been held since 2013 with philosophical themes that are rarely performed by other mosques in Yogyakarta. This study took informants from parties involved in literacy activities at the Masjid Jenderal Sudirman, such as actors and initiators of Ngaji Filsafat, mosque takmirs, and contributors who participated in the MJS literacy community (MJS Project). The method used in this research is qualitative-descriptive, with in-depth interview data collection techniques and related literature studies. In this study, the theoretical framework proposed by Jürgen Habermas is used, namely the theory of communicative action. This theory serves to explain how MJS was able to form a mosque-based literacy space through the efforts made by MJS Takmir. The researcher concluded that literacy activities at the Jenderal Sudirman Mosque originated from the Ngaji Filsafat. The analysis of the researchers' findings was based on the formation of several other activities at the Jenderal Sudirman Mosque, such as Mosque Literacy (Writing Training Class), MJS Channel, Literacy Community (MJS Project), a printing agency (MJS Press) and the Friday Bulletin.